Characterization, expression profiling, and estradiol response analysis of DMRT3 and FOXL2 in clam Cyclina sinensis - Susu Yan; Susu Yan; Mengge Xu; Mengge Xu; Jing Xie; Jing Xie; Xiaoting Liao; Xiaoting Liao; Meimei Liu; Meimei Liu; Siting Wang; Siting Wang; et al. (Frontiers in Marine Science, 2023)
The clam Cyclina sinensis is one of the important economical aquaculture shellfish in China. However, the mechanisms of sex determination and differentiation in C. sinensis have not been fully studied. In this study, full-length cDNAs of DMRT3 and FOXL2 were cloned and functionally characterized. The ORF region of CsDMRT3 consists of 1137 nucleotides, which encode 378 amino acids contains a conserved DM domain of DMRT family. The ORF region of CsFOXL2 is 1245 bp, encodes 414 amino acids, and contains a conserved FH domain. Tissue-specific expression results showed that the higher expression level of CsDMRT3 and CsFOXL2 was found in the ovary and testis of C. sinensis. The expression levels of CsDMRT3 and CsFOXL2 also peaked at the maturation stage of male and female gonadal development, respectively. Moreover, the expression levels of CsDMRT3 and CsFOXL2 were significantly higher in the trochophore and D-larval stages than in other stages. The transcript levels of CsDMRT3 reached the highest level at 11 months of age, while the CsFOXL2 reached the highest level at 7 months of age. In estradiol-treated experiments, the expression levels of CsDMRT3 and CsFOXL2 in the gonads were highest at 5 µg/L estradiol treatment, and histologically, it was observed that the oocytes diameters became larger with increasing estradiol concentration. These results suggest that CsDMRT3 and CsFOXL2 play an important role in gonadal development and sex differentiation of C. sinensis.